Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.14260/jemds/2015/2378
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Burnout Among Emergency Healthcare Workers and Factors Influencing Level of Burnout: A Study Protocol

Abstract: BACKGROUNDBurnout is a feeling of failure and exhaustion. It is felt both at the physical and emotional level. Depletion of the person's resources is a consequence and also has an impact on the organisation. Nature of the work itself makes emergency healthcare workers vulnerable to burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…One hundred seventy-six cross-sectional studies and 6 longitudinal studies involving 109 628 individuals in 45 countries published between 1991 and 2018 reporting on burnout in practicing physicians were identified (Figure 1). The number of participants per study ranged from 4 to 7830 (median, 200; interquartile range, 93-512; mean, 602). The characteristics of the full set of individual studies, the geographic regions in which they were conducted, and their Newcastle-Ottawa risk-of-bias scores appear in eTables 1 through 4 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred seventy-six cross-sectional studies and 6 longitudinal studies involving 109 628 individuals in 45 countries published between 1991 and 2018 reporting on burnout in practicing physicians were identified (Figure 1). The number of participants per study ranged from 4 to 7830 (median, 200; interquartile range, 93-512; mean, 602). The characteristics of the full set of individual studies, the geographic regions in which they were conducted, and their Newcastle-Ottawa risk-of-bias scores appear in eTables 1 through 4 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…The number of study participants ranged from 4501 in the largest study 33 to 7 in the smallest. 34 Twenty studies included other healthcare staff in addition to the medical staff participants. 9 34–52 Four studies included primary care physicians, 42 53–55 with most studies involving medical doctors from intensive or critical care, emergency departments and internal medicine ( figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies 34 35 39–41 46–48 50–53 56 57 60 64 66 67 69 71 74 used the complete Maslach Burnout Inventory (MBI) 75 ( online supplemental table 1 ). One study used a two-item ‘MBI’ 62 in an emergency department population that has been found to correlate with the full MBI in a similar population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Within this cohort 69.23% of Cataract, 55.93% Vitreoretinal and 54.54% of Glaucoma specialists indicated the highest level of burnout within this domain. With the majority aged between 31-60 79% (n = 87).…”
mentioning
confidence: 75%